Dynamics of Business Models – Strategizing, Critical Capabilities and Activities for Sustained Value Creation - Achtenhagen, Leona; Melin, Leif; Naldi, Lucia (Long range planning, 2013)
Much progress has been made recently in developing the business model concept. However, one issue remains poorly understood, despite its importance for managers, policy makers, and academics alike, namely, how companies change and develop their business models to achieve sustained value creation. Companies which manage to create value over extended periods of time successfully shape, adapt and renew their business models to fuel such value creation. Drawing on findings from a research program on continuously growing firms, this paper identifies three critical capabilities, namely an orientation towards experimenting with and exploiting new business opportunities; a balanced use of resources; as well as achieving coherence between leadership, culture, and employee commitment, together shaping key strategizing actions. Moreover, we illustrate how each of these capabilities is supported by different sets of specific activities. Jointly, these three capabilities, their activities and the strategizing actions act as complementarities for value creation. We conclude the paper by suggesting implications for research and practitioners, providing a tool for managers which allows them to reflect on and identify critical issues relevant for changing and developing their business model to sustain value creation.